2005
DOI: 10.1158/1078-0432.ccr-04-1284
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Efficacy of bcl-2 and c-myc Antisense Oligonucleotides in Combination with Cisplatin in Human Melanoma Xenografts: Relevance of the Administration Sequence

Abstract: Purpose: bcl-2 and c-myc oncogenes are frequently overexpressed in different human tumors, including melanoma. Here, we evaluate the combined efficacy of two antisense oligonucleotides targeting bcl-2 mRNA (ODN bcl-2) and c-myc mRNA (ODN c-myc) in combination with cis-diammine dichloroplatinum (cisplatin, DDP) on three human melanoma lines (LM, NG, and M20).Experimental Design: Two different sequences were designed to treat tumor-bearing mice: in the first one, ODN bcl-2 at a dose of 0.2 mg/day      4, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Combined treatment of bcl-2 and cisplatin in small-cell lung cancer [20], bladder cancer [49], mesothelioma [50] and alignant melanoma [51] showed greater effect than either one alone. Moreover, preclinical studies demonstrated potentiated antitumor efficacy of bcl-2 antisense combined with cisplatin in gastric carcinoma [52,53] and human melanoma xenografts [54]. The results of our combination treatment corroborated with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…Combined treatment of bcl-2 and cisplatin in small-cell lung cancer [20], bladder cancer [49], mesothelioma [50] and alignant melanoma [51] showed greater effect than either one alone. Moreover, preclinical studies demonstrated potentiated antitumor efficacy of bcl-2 antisense combined with cisplatin in gastric carcinoma [52,53] and human melanoma xenografts [54]. The results of our combination treatment corroborated with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…Our study shows that SMN-AS1 can be a therapeutic target, and also demonstrates the potential of combinatorial ASOs targeting distinct molecular regulators of a single gene. Combining ASOs targeting two different genes with traditional chemotherapy has been proposed for cancer therapeutics (Biroccio et al, 2003; Zupi et al, 2005), but this is the first example to our knowledge of two ASOs used in combination for a neurological disorder. Like others, we found that dosing of multiple ASOs was well tolerated in SMA mice (Hua et al, 2015; Zupi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Indeed, antisense inhibition of c-myc significantly inhibited the growth of melanoma cells in in vitro cultures 33 and improved the response to chemotherapy in human melanoma xenografts in nude mice. 34 Type I IFNs have been used as adjuvant therapy for malignant melanoma with significant but limited success and high toxicity. 35 Experimental overexpression of Myc in mouse fibroblasts and myeloblastic cells renders these cells resistant to cell cycle arrest by type I IFNs.…”
Section: Discussionmentioning
confidence: 99%